Acacia saligna's soil legacy effects persist up to 10 years after clearing: Implications for ecological restoration. (12th August 2017) - Nsikani, Mlungele M.; Novoa, Ana; van Wilgen, Brian W.; Keet, Jan‐Hendrik; Gaertner, Mirijam
Abstract: To reduce the negative impacts of invasive plants, management interventions such as control or eradication are usually necessary. It is often assumed that the impacts of invasive plants will diminish immediately after such interventions. However, in some cases the invader can have legacy effects in the soil that might persist for long periods, preventing the natural restoration of the areas managed. Therefore, to achieve the re‐establishment of a functional native ecosystem it is important to understand for how long such legacies can persist in the soil. This paper explores this issue, using Acacia saligna in South Africa as case study. We collected soil samples in invaded, non‐invaded and previously invaded sites (representing 2, 6 and 10 years after clearing) and analysed the levels of pH, carbon, nitrogen, available phosphorus, ammonium, nitrate and electrical conductivity. We also analysed enzyme activities (β‐1, 4‐glucosidase, urease and acid phosphatase). Acacia saligna invasion alters overall soil characteristics but specifically raises pH by 0.6–1.8. Moreover, soil characteristics (e.g. pH) are not restored to natural conditions after control (soil legacy effects persist up to 10 years after clearing). Furthermore, A. saligna control elevates soil NO 3 − levels and these can remain higher than in invaded (1.55–6.67 mg kg −1 ) and non‐invaded (2.16–4.35 mg kg −1 ) sites up to 10 years after clearing. Elevated NO 3 − often facilitates secondary invasion and/or weedy native species dominance which may hinder the restoration of functional native ecosystems. Therefore, strategies to manage areas previously invaded by A. saligna should take into account the removal of litter from the target invader, secondary invaders and weedy native species.